Bacterial enrichment in highly-selective acetate-fed bioreactors and its application in rapid biofilm formation. (1st March 2020) - Sun, Haohao; Mei, Ran; Zhang, Xu-Xiang; Ren, Hongqiang; Liu, Wen-Tso; Ye, Lin
Abstract: In this study, we systematically investigated the bacterial community dynamics in highly-selective (strong hydraulic selection pressure and high organic loading rate) bioreactors with acetate as the sole carbon source. 16S rRNA gene high-throughput sequencing and metagenomic sequencing results showed that phenolics-degrading bacteria (PDB), which were mainly Acinetobacter species, in the newly-formed aerobic granules could account for >70% of the total bacteria. Near full-length 16S rRNA gene sequences obtained by cloning suggest that the PDB are potentially novel species because they are distantly related to known Acinetobacter species. However, these PDB only temporarily appeared in the early stage of the granule formation and their abundance quickly decreased along the reactor operation. To retain these PDB, we demonstrated that the newly-formed aerobic granules could accelerate biofilm formation in moving bed biofilm reactors (MBBRs), and the biofilm carriers showed gradually-increased phenol degradation performance in the MBBRs. While, the bacterial community in biofilm significantly changed during the operation process of the MBBRs and the community structure became more complicated than that in the aerobic granules. Collectively, this study provides new insights into the microbial ecology of sludge granulation and biofilm formation process in the wastewater treatment systems for remediating phenolic matters. Graphical abstract: Image 1 Highlights: Bacterial community shift in highly-selective acetate-fed reactors was investigated. Acinetobacter proliferate in early stage of granule formation and decline later. A novel approach to rapidly startup MBBRs for phenol degradation was developed.